Between looking and gesturing: Pierre Hébert's concept 'animation d'observation' - Graça, Marina Estela (2012)
The French Canadian filmmaker Pierre Hébert expression ‘animation d’observation’ (literally, observation animation) first appears within the context of the production of his film Etienne et Sara (1984) and is only employed there and during the implementation of the following film project: The Subway, Songs and Dances of the Inanimate world / Le Metro, Chants et Danses du Monde Inanimé (1985). At that time, Hébert's poetics go through what is perhaps their most important transformation. Etienne et Sara, started out being the last in a series of films whose project should have been resolved in a collation of multiple graphic and moving expressions, i.e. within the scope of what we commonly call the techniques of the animated film. However, following Pierre Hébert's meeting with the Belgian poet Serge Meurant, it became evident that it was more than just a film. In Confitures de Gagaku (1986), the following production to The Subway, Songs and Dances of the Inanimate world / Le Metro, Chants et Danses du Monde Inanimé, where for the first time he is animating in the presence of the spectators, in dialogue with the saxophonist Jean Derome, the film already appears clearly as a manifestation – albeit an autonomous one – of a project which is formed in a situation of open frontiers in the collision of languages, in a precise time and space. In it the author exhibits and lays claim to the origin of the film for the body, alive and feeling, of its maker, thereby questioning the ideological workings of the whole film making machinery and protocols. In this essay I will try to explain the author’s intention when he invented and then used such verbal device within the context of his work and, broadly, that of contemporary animation.